Pembuatan Marketplace Penjualan Makanan Khas Indonesia - Gary Hans; Justinus Andjarwirawan; Silvia Rostianingsih (Jurnal Infra, 2017)
In order to expand culinary business we can use Internet as an equipment, especially for Indonesia who had large territory and variety of traditional food so to expand the business, we need a medium as tools to facilitate information coverage throughout Indonesia.The purpose of this thesis is to provide a communication medium for sellers and buyers via the Internet which is formed in a market place website. In Making Sales Marketplace for Indonesian Traditional Food, several technologies are used such as; notepad ++ software, XAMPP and browser, HTML, CSS3, PHP, and MySQL to create a database. The author also uses Facebook API to integrate technology with user social media facebook, and to get information of users' personal data.This final project has been successfully simulate an online marketplace that used as a place for sales and purchases transaction of Indonesian food products and have been successfully testing the combination of technologies that used to create this website.